The impact of comorbid COPD on survival outcomes in lung cancer patients treated with immune checkpoint inhibitors: a meta-analysis - Chen, Lin; Song, Dandan; Hou, Shufu; Liu, Aiju; Gao, Jing; Wang, Lei (Frontiers in Immunology, 2025)
BackgroundLung cancer (LC) remains the leading cause of cancer-related death worldwide. While immune checkpoint inhibitors (ICIs) have demonstrated survival benefits in advanced-stage disease, treatment responses exhibit significant heterogeneity across patients. The potential role of comorbid chronic obstructive pulmonary disease (COPD) in modulating survival outcomes from ICIs therapy remains controversial, with conflicting evidence regarding its synergistic or antagonistic effects. This meta-analysis systematically evaluates the impact of COPD on survival outcomes in lung cancer patients receiving ICIs, aiming to clarify its prognostic value and guide precision immunotherapy strategies.MethodsWe systematically searched PubMed, Cochrane Library, CNKI, and EMBASE for studies published up to March 31, 2025, to evaluate the synergistic survival impact of comorbid COPD in lung cancer patients receiving ICIs. Primary outcomes included overall survival (OS) and progression-free survival (PFS).ResultsThis study pooled data from 10 studies (N = 6,909) to assess the impact of comorbid COPD on survival outcomes among LC patients receiving ICIs. The meta-analysis revealed that LC patients with comorbid COPD showed significant improvements in OS (HR = 0.90, 95% CI: 0.85–0.96, p < 0.001) and PFS (HR = 0.54, 95% CI: 0.44–0.67, p < 0.001) compared to those without COPD. Notably, while bias analysis for PFS indicated potential bias, inter-subgroup heterogeneity was negligible (I² = 0%).ConclusionsThis study demonstrated that the presence of comorbid COPD was associated with significantly improved overall survival in lung cancer patients receiving ICIs. Although a significant progression-free survival benefit was also observed, this result may be influenced by potential publication bias. Further prospective studies that incorporate comprehensive biomarker analyses are warranted to validate the observed COPD-ICIs interaction and to develop optimized, personalized treatment strategies for this patient population.Systematic Review Registrationwww.inplasy.com, identifier INPLASY202580086.